Sweat, Soil, and Survival: A Literary Analysis of Sita Ram Adhikari’s Love Labour - Khadka, Dambar Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
Background: Nepali poetry has historically served as a vital medium for expressing cultural values, rural identity, and environmental consciousness. Within this tradition, contemporary poets like Sita Ram Adhikari contribute significantly to agrarian and ecological discourse through stylistically rich poetic works. Objective: This study aims to analyze the stylistic elements of Adhikari’s poem Love Labour, exploring how the poet’s use of diction, tone, imagery, figurative language, and structure enhances the thematic portrayal of ancestral pride, love for land, and ecological awareness. Methods: The research adopts a qualitative, text-centered approach grounded in New Criticism and Ecocriticism. Through close reading and formal analysis, the poem is examined in terms of its stylistic features and how they serve both aesthetic and environmental purposes. Findings: The analysis reveals that Adhikari employs a deceptively simple yet emotionally resonant style. His use of organic imagery, personification, metaphor, and free verse structure intensifies the poem’s themes of rural labor, cultural inheritance, and the sacredness of soil. The stylistic elements serve not only as poetic devices but as cultural and ecological signifiers. Conclusion: Love Labour exemplifies how style can shape and elevate poetic meaning. The poem's stylistic economy supports a deeper reading of environmental and socio-cultural realities in rural Nepal, reinforcing the power of poetry to preserve identity and inspire ecological thought. Novelty: This paper is one of the first academic studies to focus specifically on the stylistic analysis of Love Labour, applying both formalist and ecological lenses to a modern Nepali rural poem.